Restoring HOXD10 Exhibits Therapeutic Potential for Ameliorating Malignant Progression and 5-Fluorouracil Resistance in Colorectal Cancer - Pan, Weijie; Wang, Kaijing; Li, Jiayong; Li, Hanhua; Cai, Yuchan; Zhang, Min; Wang, Aili; Wu, Yazhou; Gao, Wei; Weng, Wenhao (Frontiers in Oncology, 2021)
Emerging evidence suggests hypermethylation of HOXD10 plays an important role in human cancers. However, the biological and clinical impact of HOXD10 over-methylation and its downstream targets in colorectal cancer remains unknown. We evaluated methylation level of HOXD10 in paired cancer and normal tissues (n=42) by using pyrosequencing, followed by validation of HOXD10 methylation status from TCGA datasets with 302 cancer tissues and 38 normal tissues. The biological function of HOXD10 was characterized in cell lines. We further evaluated the effect of HOXD10 and its targets on chemo-resistant in our established resistant cell lines and clinical cohort (n=66). HOXD10 was found frequently methylated in colorectal cancer, and its hypermethylation correlates with its low expression level, advanced disease and lymph node metastasis. Functionally, HOXD10 acts as a tumor suppressive gene, which HOXD10 expressing cells showed suppressed cell proliferation, colony formation ability and migration and invasion capacity. Mechanistically, DNMT1, DNMT3B, and MeCP2 were recruited in the HOXD10 promoter, and demethylation by 5-Aza-CdR treatment or MeCP2 knockdown can sufficiently induces HOXD10 expression. HOXD10 regulates miR-7 and IGFBP3 expression in a promoter dependent manner. Restoration of HOXD10 expression in 5-Fluorouracil (5-Fu) resistant cells significantly up-regulates expression of miR-7 and IGFBP3, and enhances chemosensitivity to 5-Fu. Conclusions: we provide novel evidences that HOXD10 is frequently methylated, silenced and contributes to development of colorectal cancers. Restoration of HOXD10 activates miR-7 and IGFBP3 expression and resulted in an inhibited phenotype biologically, suggesting its potential therapeutic relevance in CRC.